O crime de drogas e a violência em São Paulo: uma análise a partir da Lei de Drogas - Musse, Isabel Ferraz (2012)
This study analyzes the effect of Law No. 11.343/06 (Drug Law) on the crime of trafficking and possession of drugs and the relationship between drug offenses and other crimes. We explore variations due to the Drug Law through regression discontinuity designs and instrumental variables with panel data in search of a causal effect between drugs and violence. As a result, the Drug Law seems to have no significant negative impact on drug offenses. On the other hand, drug offenses have a negative association on crimes of theft and a positive relationship with crime of criminal gangs. A reduction of 100 drug offenses (per thousand inhabitants) is associated with an increase of 3.6 crimes of theft (per thousand inhabitants) and a decrease of 2.7 crimes of forming criminal gangs (per thousand inhabitants). We found no robust effects of the Drug Law on robberies, homicides, robberies followed by death, rapes, assaults and illegal gun possession.